Fa'āliyyah al-Faṣl ad-Dirāsī al-Maqlūb fī Taḥsīn Mahārat al-Kalām lit-Ṭullāb fī Madrasah Tsanawiyah Islamiyyah Hukumiyyah Level - Fadhli, Muhammad Miftah Al Aufa Ilal; Maghfurin, Ahmad; Inayah; Rahmawati, Neli Dian; Samra, Asma’ Naim Jamil Abu (Mantiqu Tayr: Journal of Arabic Language, 2026)
This study investigates the effectiveness of the Flipped Classroom model in enhancing Arabic speaking skills among eleventh-grade students at State Islamic Senior High School 1 Semarang. Given the critical importance of Arabic speaking skills for academic and professional success, despite the common challenges in acquiring these skills at the Madrasah Aliyah level, the study aims to assess the model's impact on pronunciation, intonation, fluency, vocabulary, and grammar. Employing a quasi-experimental design with a one-group pre-test/post-test procedure, 36 students participated, with 32 completing the study. Data were collected through oral performance tests and structured observations. The results indicate a significant improvement in students' Arabic speaking abilities, with the average total score rising from 14.59 in the pre-test to 17.75 in the post-test. Notable gains were observed across all evaluated areas, including pronunciation and intonation, fluency, vocabulary, and grammar. These findings suggest that the Flipped Classroom model effectively enhances speaking proficiency by promoting independent learning outside the classroom and facilitating active classroom interaction, thus improving students' readiness and confidence. This research contributes to foreign language education by demonstrating the positive impact of the Flipped Classroom model on language acquisition and offers valuable insights for educators seeking innovative teaching methods. Future research could explore the long-term effects of this model on other language skills and investigate the role of technological tools and online platforms in further enhancing language learning outcomes.